2018
DOI: 10.26822/iejee.2018438132
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Skills of Kosovar Primary School Children: A Special View on Children with Mathematical Learning Difficulties

Abstract: The present study examined the development of mathematics skills of Kosovar primary school children in terms of their gender, living area, socioeconomic status, and achievement level. A special emphasis was placed on longitudinal investigations of the development of mathematics skills in children with learning difficulties in mathematics over a 2-year and 4-month period. Participants were 553 fourth-graders, 85 of whom identified with mathematical learning difficulties were classified into two subgroups: child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
1
7
0
1
Order By: Relevance
“…Hence, students are not interested to learn mathematics, and (6) lacking motivation and counseling guidance imprecisely to learn mathematics. Economy factor stated is in line with research findings undertaken by Salihu and Räsänen [4], who claimed that students who have an excellent economic background contribute significantly toward mathematics performance. Students who have low economy background shows low mathematics ability.…”
Section: Introductionsupporting
confidence: 88%
“…Hence, students are not interested to learn mathematics, and (6) lacking motivation and counseling guidance imprecisely to learn mathematics. Economy factor stated is in line with research findings undertaken by Salihu and Räsänen [4], who claimed that students who have an excellent economic background contribute significantly toward mathematics performance. Students who have low economy background shows low mathematics ability.…”
Section: Introductionsupporting
confidence: 88%
“…Based on previous studies, the following three variables were controlled: gender, preschool attendance experiences, and SES (Anders et al, 2012;Chiu, 2018;Salihu & Räsänen, 2018;Zhu & Chiu, 2019). First, as studies have found a relationship between students' gender and their mathematics performance, gender variable was controlled (Ganley & Lubienski, 2016).…”
Section: Control Variablesmentioning
confidence: 99%
“…Participants were selected from nationally representative samples. Moreover, a structural equation modeling (SEM) was utilized to control other variables affecting students' mathematics achievement, including socioeconomic status (SES) (Salihu & Räsänen, 2018), preschool attendance experience (Anders et al, 2012), and gender (Ganley & Lubienski, 2016). In doing so, early numeracy competencies and self-efficacy beliefs were considered to mediate variables because when students have high numeracy competencies before entering school, they tend to show high mathematics achievement in elementary school (Aunio & Niemivirta, 2010;Duncan et al, 2007;Geary et al, 2018;Jordan et al, 2010;LeFevre et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, students are not familiar with non-routine problems because they usually solve routine problems, which involve the provision of examples followed by similar exercises. They normally become confused when they are provided with tests that are similar to the examples provided by teachers, thereby leading to difficulty in learning mathematics (Salihu, 2018;Wijaya et al, 2019). This usually reduces their motivation in solving these problems due to their belief that they do not have the required ability to solve the problems (Fitri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%